Efektivitas TikTok Live Streaming dalam Meningkatkan Keputusan Pembelian Konsumen Produk TUQUH Indonesia - Hafzotillah; Ibrar Panca Sanjaya; Qoute Nuraini Cahyaningrum (Jurnal Penelitian Sosial Ilmu Komunikasi, 2026)
The competitive advantage of local online shops is determined by the appropriateness of interactive marketing adoption. The Live Selling E-commerce trend integrates entertainment, personal interaction, and instant transactions into one social media platform ecosystem. This study aims to analyze the effectiveness of TikTok Live Streaming in influencing consumer purchasing decisions. The methodology used is quantitative causal-descriptive with a sample of 158 customers selected through purposive sampling technique. Instrument analysis was tested for validity and reliability, followed by classical assumption testing before the data was analyzed using simple linear regression in SPSS 25. There is a significant relationship between TikTok Live Streaming and the Purchase Decision of Tuquh Indonesia products. If the Sig. value is <0.05 then H₀ is rejected and H₁ is accepted. If the Sig. value is >0.05 then H₀ is accepted and H₁ is rejected. Based on the results of the Spearman test, a significance value of 0.000 <0.05 was obtained, so H₀ is rejected and H₁ is accepted. Thus, it can be concluded that there is a significant relationship between TikTok Live Streaming and the Purchase Decision of TUQUH Indonesia products.